Analysis of Primary Stability of Dental Implants Inserted in Different Substrates Using the Pullout Test and Insertion Torque - Nathalia Ferraz Oliscovicz; Antônio Carlos Shimano; Élcio Marcantonio Junior; César Penazzo Lepri; Andréa Candido dos Reis (International Journal of Dentistry)
The aim of the study was to evaluate mechanical behavior of implants inserted in three substrates, by measuring the pullout strength and the relative stiffness. 32 implants (Master Porous-Conexao, cylindrical, external hexagon, and surface treatment) were divided into 4 groups (n=8): pig rib bone, polyurethane Synbone, polyurethane Nacional 40 PCF, and pinus wood. Implants were installed with the exact distance of 5 mm of another implant. The insertion torque (N·cm) was quantified using the digital Kratos torque meter and the pullout test (N) was performed by an axial traction force toward the long axis of the implant (2 min/mm) through mount implant devices attached to a piece adapted to a load cell of 200 Kg of a universal testing machine (Emic DL10000). Data of insertion torque and maximum pullout force were submitted to one-way ANOVA and Bonferroni tests (α=0.05). Polyurethane Nacional 40 PCF and pinus wood showed the highest values of insertion torque and pullout force, with significant statistical difference (P<0.05) with other groups. The analysis showed stiffness materials with the highest values for primary stability.